Phyto Chemical Investigation and Determination of Crude Alkaloidal Content - Muthumani, P (International Journal of Pharmaceutical & Biological Archive, 2010)
The phytochemical studies on the plant of Solanum laeve dunal resulted in isolation of tomatilidine (16 un substituted 22,26 epiminocholestanes), Jervine being reported for the first time from this plant. These compounds have been characterized on the basis of spectral and other data. The alkaloid solosodine content present in the dry and fresh berries were determined in the isolated compounds (SA-I, SA-II, SA-III) of the extracts. The total alkaloidal content is more in SA-I compound than other compounds